Editorial note - Ahlbäck, Tore (Scripta Instituti Donneriani Aboensis, 1987)
Editorial note of Scripta Instituti Donneriani Aboensis, vol. 12, Saami Religion, based on papers read at the symposium on Saami Religion held at Åbo/Turku, Finland, on 16-18 August 1984.